The Analiysis Of Vowel"E" In The Upstream Indragiri Hulu: Analisis Bunyi Vokal "E" Pada Daerah Indragiri Hulu - Rahmawati Putri, Devita; Ardila, Della; Hayatun Maharani, Luthfi; Mukhlis, Muhammad (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
The purpose of this study is to describe the vowel sound e in the Indragiri Hulu community. This study uses document and interview methods that have been collected by the author. The research data is in the form of everyday vocabulary containing the vowel ‘e’ pepet /. This study also uses phonological theory in the pronunciation of the vowel ‘e’. The results of this study show that the vocabulary used by the community has the ending ‘e’ at the end of the vocabulary. Vocabulary that is spoken has become a characteristic of the surrounding community in vocabulary or speaking. besides that, the language of the people of Indragiri Hulu has a very prominent characteristic by getting results on the appearance of the front, middle ‘e’ vowel, by getting results that have characteristics and are not rounded. Phonological features of vowel sounds with emphasis, emphasis on the vowel ‘e’.